2024
DOI: 10.1162/rest_a_01140
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs? The Impact of WTO Accession on Intimate Partner Violence in Cambodia

Abstract: We study the impact of trade-induced changes in labor market conditions on violence within the household. We exploit the local labor demand shocks generated by Cambodia's WTO accession to assess howchanges in the employment ofwomen relative to men affected the risk of intimate partner violence. We document that men in districts facing larger tariff reductions experienced a significant decline in paid employment, whereas women in harder-hit districts increased their entry into the labor force. These changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Qualitatively, estimates on male and female unemployment support the "male backlash" theory (Macmillan & Gartner, 1999) and relates to similar findings for Spain (Tur-Prats, 2021) and Cambodia (Erten & Keskin, 2021): when man fears reduced dominance in economic terms, violence may be used to restore his authority over his partner.…”
Section: B Basic Evidencesupporting
confidence: 66%
“…Qualitatively, estimates on male and female unemployment support the "male backlash" theory (Macmillan & Gartner, 1999) and relates to similar findings for Spain (Tur-Prats, 2021) and Cambodia (Erten & Keskin, 2021): when man fears reduced dominance in economic terms, violence may be used to restore his authority over his partner.…”
Section: B Basic Evidencesupporting
confidence: 66%
“…Trade liberalization policies and the accession of China into the World Trade Organization (WTO) in 2001 have reshaped the labor markets in many developing countries (Topalova, 2007;Chiquiar, 2008;Ferreira et al, 2010;Topalova, 2010;Kovak, 2013;Dix-Carneiro and Kovak, 2017;McCaig and Pavcnik, 2018;Erten et al, 2019). Importantly, several studies have shown that the labor market e↵ects of openness to trade vary by gender (Juhn et al, 2014;Gaddis and Pieters, 2017;Ben Yahmed and Bombarda, 2020;Erten and Keskin, 2021;Mansour et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While our focus is on how DV can be prevented, there is an important line of work examining its determinants. Bhalotra et al (2021) estimate the impacts of job loss and unemployment benefits while work by Aizer (2010), Tur-Prats (2021), and Erten and Keskin (2021) has focused on local labor market conditions. Cultural factors have also been linked to DV (e.g., Alesina et al (2021), González and Rodríguez-Planas (2020), and Tur-Prats (2019)).…”
mentioning
confidence: 99%